2005
DOI: 10.1016/j.topol.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Equivariant homology and cohomology of groups

Abstract: We provide and study an equivariant theory of group (co)homology of a group G with coefficients in a Γ -equivariant G-module A, when a separate group Γ acts on G and A, generalizing the classical Eilenberg-MacLane (co)homology theory of groups. Relationship with equivariant cohomology of topological spaces is established and application to algebraic K-theory is given.It is well known that the study of groups with operators has many important applications in algebra and topology. The category of groups enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Analogues of much of the theory of the classical homological algebra of groups have been obtained in that equivariant setting such as (co)chain and cotriple presentations, the Hopf formula, exact (co)homology sequences, and the Tate cohomology of groups. Moreover, the relationship with the equivariant cohomology of spaces was established, and it was shown that the well known isomorphism of Milnor's K-group K 2 (A) with the second integral homology H 2 (E(A)) of the elementary group E(A) of a unital ring A remains true for arbitrary rings by taking into account the action on E(A) of the Steinberg group St(Z) of the ring Z of integers (see [11, Corollary 24]).As promised we continue the investigation of equivariant homology theory of H. Inassaridze [11]. Namely, using the purely algebraic method of n-foldČech derived functors developed in [7,12], we provide higher Hopf type formulas for the equivariant integral group homology (Theorem 12), extending the Hopf formula for the second equivariant homology [11] and recovering the Brown-Ellis higher Hopf formulas [2], when the group actions are trivial.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Analogues of much of the theory of the classical homological algebra of groups have been obtained in that equivariant setting such as (co)chain and cotriple presentations, the Hopf formula, exact (co)homology sequences, and the Tate cohomology of groups. Moreover, the relationship with the equivariant cohomology of spaces was established, and it was shown that the well known isomorphism of Milnor's K-group K 2 (A) with the second integral homology H 2 (E(A)) of the elementary group E(A) of a unital ring A remains true for arbitrary rings by taking into account the action on E(A) of the Steinberg group St(Z) of the ring Z of integers (see [11, Corollary 24]).As promised we continue the investigation of equivariant homology theory of H. Inassaridze [11]. Namely, using the purely algebraic method of n-foldČech derived functors developed in [7,12], we provide higher Hopf type formulas for the equivariant integral group homology (Theorem 12), extending the Hopf formula for the second equivariant homology [11] and recovering the Brown-Ellis higher Hopf formulas [2], when the group actions are trivial.…”
mentioning
confidence: 99%
“…Moreover, the relationship with the equivariant cohomology of spaces was established, and it was shown that the well known isomorphism of Milnor's K-group K 2 (A) with the second integral homology H 2 (E(A)) of the elementary group E(A) of a unital ring A remains true for arbitrary rings by taking into account the action on E(A) of the Steinberg group St(Z) of the ring Z of integers (see [11, Corollary 24]).…”
mentioning
confidence: 99%
See 3 more Smart Citations